2016 IEEE International Conference on Imaging Systems and Techniques (IST) 2016
DOI: 10.1109/ist.2016.7738208
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive multispectral GPU accelerated architecture for Earth Observation satellites

Abstract: Abstract-In recent years the growth in quantity, diversity and capability of Earth Observation (EO) satellites, has enabled increase's in the achievable payload data dimensionality and volume. However, the lack of equivalent advancement in downlink technology has resulted in the development of an onboard data bottleneck. This bottleneck must be alleviated in order for EO satellites to continue to efficiently provide high quality and increasing quantities of payload data.This research explores the selection and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…CCSDS-123 has been chosen as a case study for this research because it is the state-of-the-art lossless image compression algorithm for next generation onboard image processing, as discussed in [1]. Additionally, it is characteristically representative of other typical onboard data processing algorithms, featuring elements which are highly sequential in nature, which can be challenging to implement efficiently on GPU hardware.…”
Section: Ccsds-123 Algorithm Overviewmentioning
confidence: 99%
See 2 more Smart Citations
“…CCSDS-123 has been chosen as a case study for this research because it is the state-of-the-art lossless image compression algorithm for next generation onboard image processing, as discussed in [1]. Additionally, it is characteristically representative of other typical onboard data processing algorithms, featuring elements which are highly sequential in nature, which can be challenging to implement efficiently on GPU hardware.…”
Section: Ccsds-123 Algorithm Overviewmentioning
confidence: 99%
“…Previous work conducted has focused on identifying suitable state-of-the-art image compression algorithms and the proposal of a new GPU accelerated onboard data processing system architecture. An extensive review of image compression algorithms was conducted and is summarised in [1]. In this review, the lossless image compression algorithm CCSDS-123 was demonstrated to be one of the most suitable for onboard implementation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Traditional space qualified processors are no longer able to meet the demands of current nor future onboard data processing system requirements [4]. Therefore, as part of previous research a new onboard data processing architecture has been proposed [1]. The new GPU accelerated scalable heterogeneous hardware architecture aims to facilitate the implementation of state-of-the-art parallel image processing and compression algorithm to help alleviate the growing onboard data bottleneck of EO satellite platforms.…”
Section: Figure 2: Ccsds-123 Algorithm and Data Dependenciesmentioning
confidence: 99%
“…This is due to the importance of data fidelity to many EO data applications, particularly as computer based image processing becomes increasingly prominent for information extraction. Currently most operational satellites implement standardised algorithms such as JPEG-LS or JPEG-2000 where both these algorithms typically achieve compression ratios of approximately 2.0 [1]. However, in order to help alleviate the increasing onboard data bottleneck, new state-of-the-art compression and processing algorithms will need to be deployed to achieve increased compression ratios onboard spaceborne platforms.…”
Section: Introductionmentioning
confidence: 99%